Effect of Scots pine needle age on preference, performance, and overwintering of pine-tree lappet larvae—the distaste for the oldest foliage - Łukowski, Adrian; Giertych, Marian J.; Mąderek, Ewa; Adamczyk, Dawid; Karolewski, Piotr (Acta oecologica (Montrouge), 2022)
The choice of a host and feeding site is particularly interesting in the case of species feeding on conifers, where the larvae usually have a choice of several age classes of needles. The subject of this research is to answer whether the larvae have a specific preference for a certain needle age class, as well as how such foraging decisions influence larval performance and overwintering. We present the results of food choice tests and the influence of food quality (different age classes of Scots pine Pinus sylvestris needles) on the performance and overwintering of Dendrolimus pini larvae. The obtained results indicate that larvae fed with the youngest needles have the highest performance; however, in the food choice tests, one year old needles were chosen significantly more often. It was also shown that feeding on one year old needles led to the best overwintering survival. Differences in the contents of elements and metabolites explained the cause of the worst food, the oldest needles, and also the differentiation between current year and one year old needles. Water content may be of key importance, which is lower in one year old needles than in current year needles; its lower content may elevate the concentration of cryoprotectant substances. •Dendrolimus pini larvae fed with the youngest needles have the highest performance.•In the food choice tests, however, one year old needles were chosen significantly more often.•Feeding on one year old needles led to the best overwintering survival.•Differences in chemical composition of food explained the cause of the worst food, the oldest needles.•Our results fit a new possible scenario, which can we call: the distaste for the oldest foliage.